Rôle de la formation des enseignants du second degré sur leurs pratiques pédagogiques - Amélie Duguet; Sophie Morlaix (Recherches en Éducation)
This work aims to analyze the effect exerted by the initial and continuous training of secondary school teachers in France on their teaching practices. For this, we carry out a secondary analysis of data from the TALIS survey (Teaching and Learning International Survey), conducted in 2013 in 34 coun-tries, including France. In particular, we focus on practices related to the teaching methods used, classroom management, how to communicate, and the evaluative practices of teachers. In support of binary logistic regression models, we show that the variables related to initial training play a weak role, and even exert a negative effect on certain pedagogic practices, leading to a reflection on the renovation of this training. On the other hand, our analyzes highlight the greater weight played by certain continuing education actions.